Exchange Rate Exposure: Does exchange rate movement influence tourism development? - Abdullah, AbdulQadir Idris; Chua, Soo Yean (School of Social Sciences, USM, 2017)
This paper examines the impact of exchange rate exposure on tourism demand using a dynamic panel of 23 sub Saharan Africa’s tourist destinations. Although, the research question for the paper focuses on whether uncertainty on the exchange rate can help explain why could exchange rate fluctuation co-move with the travel expenditure using data from these selected African tourist destinations as well as the variations across countries in recent years. Utilising annual data from 1996 to 2015 on dynamic panel estimation techniques, we provide evidence which suggests that both variables exchange rate fluctuation and travel expenditure are statistically significant determinants of tourism demand. The Penal autoregressive distributed lagged ARDL panel cointegration test is utilised to examine the existence of a long run association between exchange rate and travel expenditure and the findings from the panel cointegration test reveals that real income, real xchange rates, price inflation and travel expenditure and international tourist arrival have long run relationship. We also employed pool (OLS), fixed effect (FE) and random effect (RE) models to investigate which of the models in questions can at most have useful information to explain tourism demand subject to travel expenditure with respect to the selected sampled tourist destinations in Africa.